Evaluate the possibility of creating PARK-AND-RIDE Facilities to Improve the Traffic Situation in the City of Lattakia - رستم اكرم; بشارة ميراي (Latakia University Journal -Engineering Sciences Series, 2020)
The problem of finding a suitable place for parking is One of the main problems of middle and large cities، The city of Lattakia is one of the middle cities in Syria، which has witnessed in recent years a marked increase in the population and the number of vehicles moreover to the large expansion and development in the structure of the city. The center of the city، which is concentrated in most government departments and service buildings Which design did not notice Provide suitable parking spaces so that this stand does not interfere with the movement of vehicles and pedestrians on either. The (P & R) system، which combines the best factors between the use of a private vehicle and Public transport، Which in turn enables car users to access the (P & R) facility which they can obtain the appropriate public transport services for their direct and rapid access to their destinations. The research aims to reduce traffic congestion in the center of Lattakia by reducing the use of private cars and encouraging the use of public transport. The appropriate sites should be identified for ( P & R) facilities through field questionnaire ، transport line studies and axes that are associated with the city center. Through the research، questionnaires and interviews were conducted with drivers and measuring traffic congestion at the entrance to Lattakia city to study the need for( P & R) facilities ،And a study was conducted on the public transport lines to find the sufficiency of the area and the need for private buses ، The research concluded that the (P & R) facilities should be established at the city entrance to improve the traffic situation.